2009
DOI: 10.1677/joe-09-0376
|View full text |Cite
|
Sign up to set email alerts
|

Increased bone mass in adult prostacyclin-deficient mice

Abstract: Prostaglandins (PGs) are key regulatory factors that affect bone metabolism. Prostaglandin E 2 (PGE 2 ) regulates bone resorption and bone formation. Prostacyclin (PGI 2 ) is one of the major products derived from arachidonic acid by the action of cyclooxygenase and PGI 2 synthase (PGIS). Unlike PGE 2 , there are few reports about the role of PGI 2 in bone regulation. Therefore, we investigated the potential effect of PGI 2 on bone metabolism. We used PGIS knockout (PGIS K/K ), PGIS heterozygous (PGIS C/K

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
0
12
0
1
Order By: Relevance
“…Similarly, osteocytic cells in vitro were shown to increase COX-2 expression and prostaglandin production in response to diverse mechanical stimuli including fluid flow [103, 104], substrate deformation [105] and hydrostatic pressure [34]. Of the prostaglandins, PGE 2 is the most extensively studied with respect to bone anabolic effects, although prostacyclin (PGI 2 ) has also been reported to have similar actions [106, 107]. Sorting out pathways of prostaglandin signaling between osteocytic and osteoblastic cell populations presents problems, particularly in situ , since both osteoblasts and osteocytes produce prostaglandins.…”
Section: Osteocyte-osteoblast Communicationmentioning
confidence: 99%
“…Similarly, osteocytic cells in vitro were shown to increase COX-2 expression and prostaglandin production in response to diverse mechanical stimuli including fluid flow [103, 104], substrate deformation [105] and hydrostatic pressure [34]. Of the prostaglandins, PGE 2 is the most extensively studied with respect to bone anabolic effects, although prostacyclin (PGI 2 ) has also been reported to have similar actions [106, 107]. Sorting out pathways of prostaglandin signaling between osteocytic and osteoblastic cell populations presents problems, particularly in situ , since both osteoblasts and osteocytes produce prostaglandins.…”
Section: Osteocyte-osteoblast Communicationmentioning
confidence: 99%
“…Previous work demonstrated that the prostaglandin PGE 2 can either increase bone formation and osteoblastic activity [10] or increase bone resorption [11] depending on experimental conditions. The prostaglandin, PGI 2 or prostacyclin also alters bone formation and bone resorption depending on the experimental model [12,13,14,15,16,17,18,19,20]. Deletion of prostacyclin synthase, the enzyme responsible for prostacyclin synthesis, results in a decrease in bone mineral density in young mice and an increase in bone mineral density in older mice [14].…”
Section: Introductionmentioning
confidence: 99%
“…İLLOPROST Prostasiklin; vasküler endotelyal büyüme faktö-rü salınımını stimule ederek anjiogenezi ve hücresel farklılaşmayı arttıran güçlü bir vazodilatatördür. 86,87 İlloprost ise pulmoner hipertansiyon tedavisinde kullanılan bir prostasiklin analoğudur. 88 Limjeerajarus ve ark.…”
Section: Biodentin(septodont Saint Maur Des Fossés France)unclassified